A new LNG wharf health assessment model considering structural weak areas. (June 2022) - Zhang, Chaoli; Yang, Lihao; Hu, Guanyu; Tang, Shuaiwen; Zhou, Zhijie
The structural health state of liquefied natural gas (LNG) wharf is important for the docking and operation of LNG ships. Based on the finite element modal analysis (FEMA) and evidential reasoning (ER) rule, a new health assessment model for the LNG wharf is proposed in this paper, where structural weak areas are considered. Firstly, combining the structural mechanism and FEMA, the LNG wharf is simulated and modeled. The weak areas of the wharf in common working modes are analyzed and obtained. Secondly, based on the analysis results, the sensor deployment is guided and the wharf health information is collected. Finally, based on the ER rule, the sensor monitoring information is fused to realize the health assessment of the wharf. This paper takes an LNG wharf in the Hainan Yangpu area of China as an example. The experimental results show that the proposed method can accurately and effectively assess the health state of the wharf.